EFFECTIVE APPROACHES FOR TEACHING ENGLISH FOR ESP - Aliyevna, Yuldasheva Dilorom (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
This article demonstrates some main ways and methods for teaching English for ESP students. Also, some methods and ways of having interactive and interesting during the lesson as well as some examples of the methods and their role in teaching are discussed in the following article.